'You already drank my beer, I can decide anything': using structuration theory to explore the dynamics of alcohol use, gender-based violence and HIV risk among female sex workers in Tanzania. Issue 12 (2nd December 2018) - Leddy, Anna M.; Kerrigan, Deanna; Kennedy, Caitlin E.; Mbwambo, Jessie; Likindikoki, Samuel; Underwood, Carol R.
Abstract: Female sex workers experience high rates of gender-based violence and HIV. Alcohol has been shown to facilitate women's risk of both gender-based violence and HIV; however, little research has explored how aspects of the sex work environment shape this risk. Drawing on structuration theory, this study explored how social conduct is patterned across time and space within the sex work environment to influence alcohol consumption, gender-based violence and HIV risk among female sex workers. Qualitative in-depth interviews were conducted with 24 female sex workers enrolled in an ongoing community randomised controlled trial of a combination HIV prevention intervention in Iringa, Tanzania. Data were analysed using both inductive and deductive approaches. Findings reveal how routine interactions between female sex workers and their clients occur at three moments of time and space during the sex exchange process to facilitate alcohol consumption and increase women's risk of gender-based violence and HIV. Findings also highlight how sex workers utilise collective agency to address aspects of the sex work environment that place them at risk of alcohol abuse, gender-based violence and HIV. Implications for future interventions to prevent gender-based violence and HIV among female sex workers in Tanzania and similar contexts are discussed.